(3CKQ GdSjGb aj JTcjd GdebOeI GdWddjI aj GdbUjOI GdYQHjI (B/s Remainder of title - (3CSeGA eMeO YHO GdYGWj CMeO,s; (3YHO GdMejO TjMIs (2022)
(3jSYi gPG GdHMK Edi bQGAI GdebOeGJ GdWddjI aj bUGFO GdTYQ GdLGgdj aj EWGQ GdfSb GdNGU GdPj CMGW HgG, hef nKnqe eMGhdI EKHGJ GQJHGW GdebOeI GdWddjI aj GdbUjOI GdYQHjI GdLGgdjI HgPG GdfSb(B.s
This thesis aims to analyze the ntroduction of (3z(BTalal(3y (Bruins$1 (Bdiscription of Arabic poem within the private context that surrounded it.s
(3CWQhMI (B((3eGLSJjQ(B)-(3LGeYI GdbGgQI, (B2022.s
(3HHdjhLQGajG(B: (3UaMGJ (B140-145.s
(3UOQ CjkVG cbQU eOeL(B.s
(3GdfU HGdYQHjI hGdedNU HGdEfLdjRjI(B.s
Keywords: (3GdGOHs -- (3GdYfGUQ GdGOHjI s; (3GdTYQ GdLGgdis; (3GdebOeI GdWddjIs -- (3GdSjGb GdfaSjs -- (3GdSjGb GdhLhOjs -- (3GdSjGb GdGLJeGYjs